Anomalous pulmonary venous drainage due to malposition of septum primum: two case reports and literature review - Yang, Yan; Zhao, Jianshe; Dong, Chunhua; Yi, Minggang; Gao, Xin (Frontiers in Pediatrics, 2024)
Background Anomalous pulmonary venous connection with malposition of septum primum (MSP) is a rare pediatric cardiovascular malformation. Although reports in the literature are scarce, accurate pre-operative imaging diagnosis is crucial for selecting the appropriate clinical intervention and determining the prognosis for affected children. Case description In both case reports, the cardiovascular malformations were incidental findings. In the second case, an enlarged cardiac silhouette was observed on chest x-ray due to pneumonia, which was subsequently confirmed by ultrasound. Combined with computed tomography angiography examination, the diagnosis of MSP-type anomalous pulmonary venous connection was established. Conclusions Comprehensive imaging examinations are essential in reducing misdiagnosis and achieving an accurate diagnosis of MSP-type anomalous pulmonary venous connection. The typical imaging findings for MSP-type anomalous pulmonary venous connection include absence or hypoplasia of the superior limbic band of the septum secundum, leftward displacement of the septum primum, and partial or total pulmonary vein drainage into the anatomical right atrium.